PELATIHAN OPTIMASI PEMASARAN ONLINE DENGAN MEMANFAATKAN SEARCH ENGINE OPTIMIZATION (SEO) PADA KOMUNITAS PENGUSAHA MUDA - Rizky Tahara Shita; Lauw Li Hin; Anita Diana; Dwi Achadiani; Fatmasari Fatmasari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The existence of a online market has become a common thing and has its own market share. Some of the factors that make entrepreneurs switch to the online market, among others, are wider marketing at a lower cost and more targeted. For this reason, it is necessary to improve online marketing techniques to increase the income of entrepreneurs. Some of the obstacles experienced by the Young Entrepreneurs Community (KPM) include the not yet maximal knowledge of online marketing of business products, especially online marketing optimization techniques with the Google search engine, and the lack of maximum training facilities among KPM. Therefore, in this community service activity, training on online marketing optimization techniques by utilizing the Google search engine for KPM circles is needed, so that young entrepreneurs can utilize and apply it in their business. The training committee team carried out a series of stages in the preparation of this training, namely by observing, then interviewing, and studying the literature. Then the methods, theoretical explanations and practicals directly to the participants, were applied during the training. As a result, KPM circles can find out the introduction of online businesses and optimize their business through search engines, thus helping partners in realizing the vision and mission of KPM itself. KPM circles can also save on marketing costs and are more targeted than conventional marketing methods.